The Addition of Mango and Papaya Peels to Corn Extrudates Enriches Their Phenolic Compound Profile and Maintains Their Sensory Characteristics - Fontes-Zepeda, Alejandro; Lopez Diaz, Jose Alberto; Domínguez-Avila, Jesus Abraham; Lopez-Martinez, Leticia; Cruz-Valenzuela, Reynaldo; Robles-Sánchez, Maribel; Salazar-López, Norma; Ramírez-Wong, Benjamin; Pareek, Sunil; Villegas-Ochoa, Mónica; González-Aguilar, Gustavo Adolfo (2022)
Purpose To determine the viability of using fruit peels to supplement extruded snacks that are rich in phytochemicals, and of good sensory characteristics and acceptability, thereby minimizing agro-industrial waste while also obtaining a value-added product. Methods Corn extrudates with 15% mango or papaya peel and their combinations were formulated; phenolic compounds, total carotenoids, antioxidant capacity, physicochemical characteristics, sensory acceptability, bioaccessibility and apparent absorption of their bioactive compounds were analyzed. Results Corn extrudates with mango peel (15%) showed higher overall acceptability, their total phenolic content increased approximately fourteen times (from 0.24 to 3.33 mg GAE/g) and their antioxidant capacity up to 5.3 times, as compared to the control. They were also enriched with catechin, mangiferin and quercetin-3-β-glucoside, neither of which were found in control samples. Papaya peel increased their carotenoid concentration (17.46 µg β-CE/g). During in vitro digestion, the release of bioactive compounds and antioxidant capacity was highest during the intestinal stage. Extrudates that contained more mango peel showed higher percentages of bioaccessibility, apparent absorption of bioactive compounds and antioxidant capacity during in vitro digestion. Conclusion Mango and papaya peels can be successfully incorporated into corn-based extruded snacks, resulting in higher concentration of bioactive compounds and without compromising sensory acceptability.